Ureteroscopy-Assisted Retrograde Nephrostomy (UARN) after Anatrophic Nephrolithotomy - Takashi Kawahara; Hiroki Ito; Hideyuki Terao; Yoshitake Kato; Takehiko Ogawa; Hiroji Uemura; Yoshinobu Kubota; Junichi Matsuzaki (Case Reports in Medicine)
Introduction. Open surgical anatrophic nephrolithotomy (ANL) had been the standard treatment for large renal calculi prior to the development of endoscopic devices and endoscopic techniques. A previous report described the efficacy of ureteroscopy-assisted retrograde nephrostomy (UARN) and presented a case of renal calculi successfully treated with UARN during percutaneous nephrolithotomy (PCNL) in a patient after ANL. Case Presentation. A 61-year-old male with left renal calculi was referred for further treatment. The patient was placed under general and epidural anesthesia, in a Galdakao-modified Valdivia position. A flexible ureteroscope (URS) was inserted, and a Lawson retrograde nephrostomy puncture wire was advanced into the flexible URS. The puncture wire then followed the route from the renal pelvis to the exit skin. Calculus fragmentation was undertaken using a pneumatic lithotripter. Conclusions. UARN for PCNL was therefore found to be a safe, effective, and appropriate treatment for a patient presenting with renal calculi after undergoing ANL.